Geopostors: A Real-Time Geometry/Impostor Crowd Rendering System: - DOBBYN, SIMON; O'SULLIVAN, ANN CAROL; Hamill, David; O'Conor, keith (ACM Press, 2005)
The simulation of large crowds of humans is important in many fi elds of computer graphics, including real-time applications such as games, as they can breathe life into otherwise static scenes and enhance believability. We present a novel hybrid rendering system for crowds that solves the classic problem of degraded quality of image-based representations at close distances by building an impostor rendering system on top of a full, geometry-based, human animation system. This enables almost imperceptible switching between the two representations based on a pixel to texel ratio, with minimal popping artefacts. Seamless interchanges are further facilitated by exploiting programmable graphics hardware to efficiently enhance the realism and variety of the dynamically-lit impostors, thereby also improving on existing impostor techniques. To test our system, our virtual crowds are embedded in an urban simulation system (as shown in Figure 1). The results demonstrate a system capable of rendering large realistic crowds with the visual realism of a high-resolution geometry rendering system, but at a fraction of the rendering cost.
Proceedings of the ACM SIGGRAPH 2005 Symposium on Interactive 3D Graphics and Games (SI3D)
PUBLISHED
Keywords: Computer Graphics; human modeling and animation; simplification; level of detail; image-based rendering; Virtual Reality